Efficacy and safety of low‐dose apatinib in ovarian cancer patients with platinum‐resistance or platinum‐refractoriness: A single‐center retrospective study. (6th July 2020) - Chen, Wei; Li, Ziting; Zheng, Zhong; Wu, Xiaohua
Abstract: Background: This study aimed to evaluate the efficacy and safety of apatinib with a low dose of 250 mg/d in the treatment of platinum‐resistant or platinum‐refractory ovarian cancer patients. Methods: Patients with platinum‐resistant or platinum‐refractory ovarian carcinoma treated with 250 mg/d apatinib in our institution from November 2016 to December 2017 were retrospectively reviewed. The tumor response and progression were evaluated according to the standard by incorporating the levels of CA125 and Response Evaluation Criteria in Solid Tumors 1.1. CTCAE 4.03 was used to evaluate adverse events (AEs). Results: Fifty‐two eligible patients were enrolled in per‐protocol (PP) analysis and 65 patients (including 13 lost to follow‐up) were included in the intention‐to‐treat (ITT) analysis. In PP analysis, 18 patients (34.6%) had partial response (PR), 22 patients (42.3%) had stable disease (SD), and the disease control rate (DCR) was 61.5%. Median progression‐free survival (PFS) was 4.0 months (95% CI, 2.83‐5.17 m), and median overall survival (OS) was 25.33 months (95% CI, 17.74‐32.92 m). The objective response rate and DCR for patients in ITT analysis were 27.7% and 49.2%, respectively. The top three treatment‐related AEs were hypertension, hand‐foot syndrome, and leukopenia. Eight patients (15.4%) in PP population had grade 3 treatment‐related AEs. Previous chemotherapy lines, number of recurrences, and AEs did not affect the efficacy of apatinib. Age older than 60 was associated with higher rates of disease control and prolonged PFS ( P  < .05). Conclusion: Apatinib 250 mg/d is a feasible treatment in platinum‐resistant or platinum‐refractory epithelial ovarian cancer (EOC) patients. Abstract : Apatinib 250 mg/day is a feasible treatment in patients with platinum‐resistant or platinum‐refractory EOC.